Comparação dos efeitos sobre o assoalho pélvico da técnica de pilates associada ou não com à contração muscular voluntária do assoalho pélvico - Souza, Luiza Torelli de [UNIFESP] (2015)
Objective: The purpose of this study was to evaluate the effectiveness of adding voluntary pelvic floor muscle (PFM) contraction to the Pilates exercise program. Methods: An assessor-blinded randomized controlled trial. Fifth seven healthy nulliparous and physically inactive women were randomized to Pilates exercise program with or without voluntary pelvic floor muscle (PFM) contraction. Forty eight women concluded this study (twenty four participants for each group). The evaluation included assessments of PFM function at baseline and post 24 sessions of Pilates exercise program. The PFM function was recorded by a physiotherapist (PT1) using a Perineometer and vaginal palpation (Oxford Scale) and pubovisceral muscle thickness and the levator hiatus (LA) area were measured by US- 3D for this evaluation process was performed consisted by one Urogynecologist (UG) .Both professional were blinded to the group allocation. After the evaluation, volunteers were randomized in two groups: Pilates exercised (PE) (n=24) or Pilates exercises associated with voluntary PFM contraction (PE+PFM) (n=24). The protocol of both groups consisted of 24 biweekly 1-h sessions of individual and standardized Pilates program, performed by a physiotherapist specialized in PFM rehabilitation and Pilates technique (PT2). The pelvic floor muscle function measured by digital palpation and vaginal pressure measurement . Pubovisceral muscle thickness and the levator hiatus (LA) area were measured by ultrasound 3D. Both groups performed the same protocol. However, the physiotherapist requested the voluntary PFM contraction during Pilates exercises of PE+ PFMC group. Results:The group PE+PFM showed significantly greater functional improvements than did the group PE. When comparing Oxford scale, vaginal pressure and thickness pubovisceral muscle measurements at baseline and post treatment. Conclusions: Our findings suggest that adding the voluntary contraction to the Pilates exercise program is more effective than standardized Pilates to improve the PFM function and pubovisceral muscle.